SPEACH ACTIONS IN JAVANESE LANGUAGE LEARNING CLASS X IN SMK CIPTA KARYA PREMBUN KEBUMEN - Wibowo, Rahmat Aji (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2022)
This study aims to describe the types of speech acts that appear in activities in class X learning speaking in the 2016/2017 academic year at SMK Cipta Karya and the function of speech acts in learning speaking for class X in the academic year 2016/2017 at SMK Cipta Karya Prembun. This study used descriptive qualitative method. The research subjects were students of class X SMK Cipta Karya Prembun. The data collected comes from speech acts and Javanese language learning in class X SMK Cipta Karya Prembun. The data analysis of this research is the equivalent method. The results showed that the speech acts found in the discussion activities in Javanese language learning class X SMK Cipta Karya Prembun seen from the purpose of the acts from the speaker’s point of view were locutionary speech acts 114 utterances, illocutionary speech acts 160 utterances and perlocutionary speech acts 4 utterances. The function of speech acts found in discussion activities in Javanese language learning class X SMK Cipta Karya is the function of informing 89 utterances, asking 24 utterances, commanding 7 utterances, refuting 2 utterances, stating 67 utterances, mentioning 2 utterances, asking for 12 utterances, thanking 3 utterances., apologized 4 speeches, greeted 53 speeches, made 2 speeches happy, supported 1 speech and completed 1 speech.